2021
DOI: 10.3390/vaccines9080880
|View full text |Cite
|
Sign up to set email alerts
|

VENUS, a Novel Selection Approach to Improve the Accuracy of Neoantigens’ Prediction

Abstract: Neoantigens are tumor-specific antigens able to induce T-cell responses, generated by mutations in protein-coding regions of expressed genes. Previous studies demonstrated that only a limited subset of mutations generates neoantigens in microsatellite stable tumors. We developed a method, called VENUS (Vaccine-Encoded Neoantigens Unrestricted Selection), to prioritize mutated peptides with high potential to be neoantigens. Our method assigns to each mutation a weighted score that combines the mutation allelic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…We have previously shown that adenovirus vectored neoAg vaccines prevent tumor development in a prophylactic setting and cure large established tumors when used in combination with CPI in a therapeutic setting in different mouse tumor models. 4 , 6 , 11 Here, we confirmed our previous findings by generating a new vaccine targeting 31 neoAgs selected from the CT26 mouse colon cancer cells (Ad-CT26; Table 1 ; materials and methods ) by using the VENUS algorithm, a recently described bioinformatic tool that uses DNA and RNA NGS data to prioritize mutated peptides with high potential to be neoAgs. 11 …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We have previously shown that adenovirus vectored neoAg vaccines prevent tumor development in a prophylactic setting and cure large established tumors when used in combination with CPI in a therapeutic setting in different mouse tumor models. 4 , 6 , 11 Here, we confirmed our previous findings by generating a new vaccine targeting 31 neoAgs selected from the CT26 mouse colon cancer cells (Ad-CT26; Table 1 ; materials and methods ) by using the VENUS algorithm, a recently described bioinformatic tool that uses DNA and RNA NGS data to prioritize mutated peptides with high potential to be neoAgs. 11 …”
Section: Resultssupporting
confidence: 84%
“… 4 , 6 , 11 Here, we confirmed our previous findings by generating a new vaccine targeting 31 neoAgs selected from the CT26 mouse colon cancer cells (Ad-CT26; Table 1 ; materials and methods ) by using the VENUS algorithm, a recently described bioinformatic tool that uses DNA and RNA NGS data to prioritize mutated peptides with high potential to be neoAgs. 11 …”
Section: Resultssupporting
confidence: 84%
“…Compared to the other pipelines, ease of use was also an advantage of Seq2Neo, since the Seq2Neo model provides a one-stop solution for neoantigen prediction using raw sequencing data. To demonstrate the performance of Seq2Neo, we applied Seq2Neo to samples from five cancer patients with experimentally validated neoantigenic mutations [ 34 , 35 , 36 , 37 ]. Those cancer samples contained WES, RNA-seq data and 16 experimentally validated neoantigenic DNA sites ( Figure S3A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…As tumors can accumulate hundreds of mutations, bioinformatic algorithms have been developed to select the ‘best’ candidates and prioritize those with the highest probability of inducing T-cell responses [ 17 ]. The allelic frequency of the mutation, the abundance of the RNA transcript coding for the mutation and the theoretical MHC-binding affinity of the mutated peptide are the most commonly used parameters for the selection [ 18 ]. Single nucleotide variant mutations (SNVs) represent the major source of neoantigens, followed by nucleotide insertions or deletions (indels).…”
Section: Clinical Experience With Personalized Vaccines In Melanoma P...mentioning
confidence: 99%